Custom‐made design of metabolite composition in N. benthamiana leaves using CRISPR activators. Issue 8 (5th June 2022) - Selma, Sara; Sanmartín, Neus; Espinosa‐Ruiz, Ana; Gianoglio, Silvia; Lopez‐Gresa, Maria Pilar; Vázquez‐Vilar, Marta; Flors, Victor; Granell, Antonio; Orzaez, Diego
Summary: Transcriptional regulators based on CRISPR architecture expand our ability to reprogramme endogenous gene expression in plants. One of their potential applications is the customization of plant metabolome through the activation of selected enzymes in a given metabolic pathway. Using the previously described multiplexable CRISPR activator dCasEV2.1, we assayed the selective enrichment in Nicotiana benthamian a leaves of four different flavonoids, namely, naringenin, eriodictyol, kaempferol, and quercetin. After careful selection of target genes and guide RNAs combinations, we created successful activation programmes for each of the four metabolites, each programme activating between three and seven genes, and with individual gene activation levels ranging from 4‐ to 1500‐fold. Metabolic analysis of the flavonoid profiles of each multigene activation programme showed a sharp and selective enrichment of the intended metabolites and their glycosylated derivatives. Remarkably, principal component analysis of untargeted metabolic profiles clearly separated samples according to their activation treatment, and hierarchical clustering separated the samples into five groups, corresponding to the expected four highly enriched metabolite groups, plus an un‐activated control. These results demonstrate that dCasEV2.1 is a powerful tool for re‐routing metabolic fluxes towards the accumulation of metabolites of interest, opening the door for the custom‐made design of metabolic contents in plants.